2013
DOI: 10.1002/14651858.cd010567.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic drugs for neuropathic pain and fibromyalgia - an overview of Cochrane reviews

Abstract: Antiepileptic drugs for neuropathic pain and fibromyalgia-an overview of Cochrane reviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
145
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 207 publications
(164 citation statements)
references
References 88 publications
(12 reference statements)
0
145
0
7
Order By: Relevance
“…12 Anticonvulsant medicines such as gabapentin and pregabalin, sometimes called gabapentinoids, have been shown to be effective in neuropathic pain conditions such as diabetic peripheral neuropathy. 13 However, the evidence for the efficacy and safety of anticonvulsants in low back and lumbar radicular pain is unclear and can be resolved only by high-quality evidence produced from placebo-controlled trials. Previous reviews were limited only to populations with chronic back pain, 14 and new evidence may affect conflicting and limited conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…12 Anticonvulsant medicines such as gabapentin and pregabalin, sometimes called gabapentinoids, have been shown to be effective in neuropathic pain conditions such as diabetic peripheral neuropathy. 13 However, the evidence for the efficacy and safety of anticonvulsants in low back and lumbar radicular pain is unclear and can be resolved only by high-quality evidence produced from placebo-controlled trials. Previous reviews were limited only to populations with chronic back pain, 14 and new evidence may affect conflicting and limited conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…Although gabapentin and pregabalin are used in this condition (Traynor et al, 2011;Wiffen et al, 2013), a systematic review of clinical trials for gabapentin concluded that there was currently insufficient evidence to confirm its efficacy (Moore et al, 2014).…”
mentioning
confidence: 99%
“…Currently, pregabalin and duloxetine are the only medications specifically approved for DPNP (2). Their clinical effect is modest, with the number needed to treat (NNT) for one extra patient to achieve 50% reduction in pain over placebo being 6.3 (95% CI 4.6, 10) for 600 mg/day pregabalin, 11 (95% CI 6.1, 54) for 300 mg/day pregabalin (6), and 5 (95% CI 4, 7) for duloxetine (7). Although neuropathic pain appears to be relatively unresponsive to opioid analgesics, some evidence demonstrates efficacy of strong opioids (oxycodone and morphine) in neuropathic pain states, including DPNP (8,9).…”
mentioning
confidence: 99%